The Role of Joint Auditing in Improving the Quality Characteristics of Accounting Information - Hayder Mohammed Ali Yousif (International Forum of Researchers and Lecturers, 2024)
The study intends to define the idea of joint auditing, its significance and goals, and the allocation of audit responsibilities from the start of the audit process to the joint report's writing. It also seeks to elucidate the function of joint auditing in enhancing the caliber of the attributes of accounting data, which helps to provide high-quality information that benefits management and the beneficiaries of that information to make sound decisions that benefit the development of the institution's work for management and owners on the one hand and benefit investors on the other hand, as the study sample included a group of auditors In Iraq by creating and designing a questionnaire form and presenting it to a panel of arbitrators; data analysis was conducted using the statistical analysis software SPSS; and the findings were examined, an important role was reached for joint auditing in improving accounting information and the study recommended the need to adopt this type of audit method that increases users' confidence in accounting information.